2013
DOI: 10.1016/j.cell.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Inhibit the Translation of Target mRNAs on the Endoplasmic Reticulum in Arabidopsis

Abstract: Translation inhibition is a major but poorly understood mode of action of micro(mi)RNAs in plants and animals. In particular, the subcellular location where this process takes place is unknown. Here we show that the translation inhibition but not the mRNA cleavage activity of Arabidopsis miRNAs requires ALTERED MERISTEM PROGRAM1 (AMP1). AMP1 encodes an integral membrane protein associated with endoplasmic reticulum (ER) and ARGONAUTE1, the miRNA effector and a peripheral ER membrane protein. Large differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
424
0
10

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(459 citation statements)
references
References 68 publications
17
424
0
10
Order By: Relevance
“…However, the finding of many miRNA-directed slicing events in Nematostella does not mean that bilaterianlike interactions between the miRNA seed and other transcript targets do not occur in parallel. Moreover, extended miRNA-mRNA matches in plants leading to target slicing were recently shown also to promote substantial translational inhibition, and it is possible that the same also occurs in Cnidaria (Brodersen et al 2008;Yang et al 2012;Li et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, the finding of many miRNA-directed slicing events in Nematostella does not mean that bilaterianlike interactions between the miRNA seed and other transcript targets do not occur in parallel. Moreover, extended miRNA-mRNA matches in plants leading to target slicing were recently shown also to promote substantial translational inhibition, and it is possible that the same also occurs in Cnidaria (Brodersen et al 2008;Yang et al 2012;Li et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This contradicts a substantial amount of empirical data. Many plant miRNA targets that are perfectly paired in the central region are nonetheless also translationally repressed (Chen, 2004;Yang et al, 2011;Li et al, 2013). Conversely, not all targets that do have central mismatches are translationally repressed: Some are non-coding RNAs that are still sliced despite the central mismatches (Allen et al, 2005), some act as targetmimics (Ivashuta et al, 2011;Liu et al, 2014), while others are simply non-functional, especially when the miRNA levels are not overwhelming (Li et al, 2014a).…”
Section: Conservation and Identification Of Mirna Targetsmentioning
confidence: 99%
“…By contrast, plant miRNAs are highly complementary to their targets, and cleavage in the middle of target sites is the major mode of plant miRNA action (Rhoades et al, 2002). However, growing evidence indicates that plant miRNAs can also inhibit the translation of their targets (Brodersen et al, 2008;Iwakawa and Tomari, 2013;Li et al, 2013bLi et al, , 2013cLiu et al, 2013). In vitro assays of RNA-induced silencing complexes containing Arabidopsis thaliana ARGONAUTE1 (AGO1) demonstrated that plant miRNAs can repress translation initiation uncoupled with deadenylation or mRNA decay (Iwakawa and Tomari, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, miRNA binding sites in ORFs can hinder the movement of ribosomes (Iwakawa and Tomari, 2013). In Arabidopsis, miRNA-mediated translation repression occurs in the endoplasmic reticulum and requires the endoplasmic reticulum protein ALTERED MERISTEM PROGRAM1 (Li et al, 2013c).…”
Section: Introductionmentioning
confidence: 99%